Edad, juventud y acceso a responsabilidades sociales (Portugal, siglos XVI-XVIII) - Olival, Fernanda (2019)
This chapter describes the state of the art on the history of youth in Portugal and shows the lack of studies, if the education history is excluded. On this stage of life, it is analyzed the following topics (16-18th centuries), using juridical sources, mostly: age requirements for access to occupations and social distinctions; meaning of these referents for different social groups; used terminology and age proofing instruments.